Students' preparation in IELTS Writing Task 1: How to write a summary of visual information - Fitria, Tira Nur (LingTera, 2024)
The International English Language Testing System (IELTS) Writing Task  1 is used to test participants' ability to select and report main ideas, describe and compare data, identify trends in factual information, or describe a process. This research describes the types of questions in IELTS Writing Task 1 and how to write a summary of visual information usually in the form of a graph, chart, or diagram in IELTS Writing Task 1.  This research uses a descriptive qualitative approach. The analysis shows that IELTS Academic Writing Task 1 emphasizes graph interpretation and analysis. In this activity, verbal proficiency must be multiplied by the ability to comprehend and represent information as graphs (graphicacy). The provided information may be directly reflective of what we see (as in pictures or drawings) or more abstract, such as spatial (maps, plans, and diagrams) or numerical (charts, graphs, and tables) information (as in tables and graphs. There are several types of IELTS Writing Task 1, for example, pie charts, bar charts, bar graphs, line graphs, tables, maps, diagram processes, line and bar charts, also pie and bar charts. Each form of data visualization has its way of describing it.  To complete the IELTS Writing Task 1, participants are required to write a minimum of 150 words of writing or an essay. We can divide the number of words into 3 paragraphs (introduction, body, and conclusion) to make it easier to write an essay according to the data presented. The IELTS Writing Task 1 can be fairly challenging, particularly if we have not prepared. Overcoming these challenges requires good preparation, consistent practice, and a deep understanding of the IELTS format, structure, and requirements.